Stocks for All People's Capitalism in the Twenty-First Century - Mäntysaari, Petri (De Gruyter, 2021)
Public stock markets are too small. This book is an effort to rescue public stock markets in the EU and the US. There should be more companies with publicly-traded shares and more direct share ownership. Anchored in a broad historical study of the regulation of stock markets and companies in Europe and the US, the book proposes ways to create a new regulatory regime designed to help firms and facilitate people's capitalism.